ANALISIS PENGARUH RESIKO PERBANKAN DAN KEBIJAKAN MONETER TERHADAP KEMAMPUAN PERBANKAN DALAM PENYALURAN KREDIT - Ronal Colin; Syarief Fauzie (Ekonomi dan Keuangan, 2014)
The purpose of this study is to investigate and analyze the effect of bank risk (the ratio of loan-loss provisions and expected default frequency) and bank-specificcharacteristics (the ratio of capital, size and liquidity) to bank lending channel at conventional commercial banks in Indonesia and to investigate and analyze the effect of bank risk (the ratio of loan-loss provisions and expected default frequency) and bank-specificcharacteristics (the ratio of capital, size and liquidity) to bank lending channel with interest rate of Bank Indonesia Certificates as a moderating variable.Secondary data collection is done by downloading the data published financial statementsconventional bank on www.bi.go.id and the data bonds obtained from the Indonesia Bond Pricing Agency. This study employs panel regression model for the first hypothesis testing and analysis of moderating variable regression model with residual method for the second hypothesis testing.The results of the study indicate that the first hypothesis is jointly bank risk (the ratio of loan - loss provisions and expected default frequency) and the bank-specificcharacteristics (the ratio of capital, size and liquidity) have significant impact towards bank lending channel at conventional commercial banks in Indonesia. Partial test showed that the independent variables are liquidity has no effect on bank lending channel. In the second hypothesis the results showed that the interest rate of Bank Indonesia Certificates moderate the effect of size to bank lending channel and also moderate the effect expected default frequency to bank lending channel. However, the interest rate of Bank Indonesia Certificates not moderate the effect of loan-loss provisions to bank lending channel, the effect of capital to bank lending channel, as well as liquidity to the lending bank channel.Keywords : loan - loss provisions, expected default